The production of a key floral volatile is dependent on UV light in a sexually deceptive orchid - Falara, Vasiliki (Oxford University Press, 2013)
BACKGROUND AND AIMS: Plants use a diverse range of visual and olfactory cues to advertize to pollinators. Australian Chiloglottis orchids employ one to three related chemical variants, all 2,5-dialkylcyclohexane-1,3-diones or ‘chiloglottones’ to sexually attract their specific male pollinators. Here an investigation was made of the physiological aspects of chiloglottone synthesis and storage that have not previously been examined. METHODS: The location of chiloglottone production was determined and developmental and diurnal changes by GC-MS analysis of floral tissue extracts was monitored in two distantly related Chiloglottis species. Light treatment experiments were also performed using depleted flowers to evaluate if sunlight is required for chiloglottone production; which specific wavelengths of light are required was also determined. KEY RESULTS: Chiloglottone production only occurs in specific floral tissues (the labellum calli and sepals) of open flowers. Upon flower opening chiloglottone production is rapid and levels remain more or less stable both day and night, and over the 2- to 3-week lifetime of the flower. Furthermore, it was determined that chiloglottone production requires continuous sunlight, and determined the optimal wavelengths of sunlight in the UV-B range (with peak of 300 nm). CONCLUSIONS: UV-B light is required for the synthesis of chiloglottones – the semiochemicals used by Chiloglottis orchids to sexually lure their male pollinators. This discovery appears to be the first case to our knowledge where plant floral odour production depends on UV-B radiation at normal levels of sunlight. In the future, identification of the genes and enzymes involved, will allow us to understand better the role of UV-B light in the biosynthesis of chiloglottones.